2007
DOI: 10.1002/nur.20197
|View full text |Cite
|
Sign up to set email alerts
|

Patient involvement in health‐related decisions during prolonged critical illness

Abstract: We describe patterns of communication of patients involved in health-related decision making during prolonged mechanical ventilation (PMV). Data were collected using observation, interview, and record review. Twelve of 30 patients participated in decisions about initiating, withdrawing, and withholding life-sustaining treatment, surgery, artificial feeding, financial/legal issues, discharge care, and daily care procedures. Patient involvement was largely validation or confirmation of what clinicians and famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 51 publications
0
41
0
Order By: Relevance
“…Within the area of withdrawing or withholding life‐sustaining treatment, patients in ICU are involved in decisions regarding artificial nutrition (Happ et al , 2007). Our study shows that some patients are involved in nutritional decisions when they are feeling slightly better, while others are handing over the care to the professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Within the area of withdrawing or withholding life‐sustaining treatment, patients in ICU are involved in decisions regarding artificial nutrition (Happ et al , 2007). Our study shows that some patients are involved in nutritional decisions when they are feeling slightly better, while others are handing over the care to the professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Developing evidence-based approaches to assist patients with life-limiting illness and their families facing multiple complex decisions over time is a palliative care research priority. [6][7][8][9][10][11][12][13][14][15][16] A recent National Cancer Institute report, Patient-centered Communication in Cancer Care: Promoting Healing and Reducing Suffering, identified deficits in communication around decision making across the trajectory of cancer. 17 The main research gaps identified were the need to include discussion of alternative options such as forgoing cancer treatment, surrogate decision making, and decision making as the end of life (EOL) approaches.…”
mentioning
confidence: 99%
“…Weaning attempts were unsuccessful if the patient was returned to full ventilatory support. Description of the design and findings of the parent study have been reported elsewhere 2730. Consistent with an exploratory sequential mixed methods approach, the results of the first, qualitative study describing the practices and beliefs about bathing patients during PMV weaning were used to inform and shape this follow-up, quantitative study which measured prevalence of a phenomenon (bathing patterns) described in the qualitative phase 31.…”
Section: Methodsmentioning
confidence: 99%